THE EFFECTIVENESS OF KNOW-WANT-LEARNED AND COLLABORATIVE STRATEGIC READING STRATEGIES TO TEACH READING COMPREHENSION TO STUDENTS WITH POSITIVE AND NEGATIVE ATTITUDES - Rosari, Lia; Mujiyanto, Yan (Universitas Negeri Semarang, 2016)
This study was an experimental research aimed at examining the effectiveness of Know-Want-Learned and Collaborative Strategic Reading strategies to teach reading comprehension to the eleventh grade students with positive and negative attitudes in SMAN 2 Mranggen, Demak. I used closed-ended questionnaire, observation checklist, and interview to categorize the students’ attitudes into positive and negative. Meanwhile, I used reading comprehension test to test the students’ ability in reading comprehension. The study revealed five results. First, KWL was more effective to students with positive attitudes. Second, CSR was more effective to students with positive attitudes. Third, none was more effective between KWL and CSR strategies to students with positive attitude. Fourth, CSR was more effective than KWL to students with negative attitudes. The last, there was no significant interaction between the strategies and attitudes to teach reading comprehension. However, it could be said that the significance was low. In conclusion, this study has proven that KWL and CSR could help the students in reading comprehension for both students with positive and negative attitudes.